2016
DOI: 10.1186/s12936-016-1394-3
|View full text |Cite
|
Sign up to set email alerts
|

Is Nigeria winning the battle against malaria? Prevalence, risk factors and KAP assessment among Hausa communities in Kano State

Abstract: BackgroundMalaria is one of the most severe global public health problems worldwide, particularly in Africa, where Nigeria has the greatest number of malaria cases. This community-based study was designed to investigate the prevalence and risk factors of malaria and to evaluate the knowledge, attitudes, and practices (KAP) regarding malaria among rural Hausa communities in Kano State, Nigeria.MethodsA cross-sectional community-based study was conducted on 551 participants from five local government areas in Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
165
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(197 citation statements)
references
References 73 publications
29
165
3
Order By: Relevance
“…This outcome is consistent with the findings in a study conducted in Kano and Sokoto states in 2016 which showed that respondents had good levels of knowledge and attitudes regarding malaria transmission, symptoms, and prevention [11] [14]. The limitation of this study was that those interviewed to assess their knowledge of malaria preventive measures were not necessary patients who received treatment at the health facility during the malaria outbreak.…”
Section: Discussionsupporting
confidence: 88%
“…This outcome is consistent with the findings in a study conducted in Kano and Sokoto states in 2016 which showed that respondents had good levels of knowledge and attitudes regarding malaria transmission, symptoms, and prevention [11] [14]. The limitation of this study was that those interviewed to assess their knowledge of malaria preventive measures were not necessary patients who received treatment at the health facility during the malaria outbreak.…”
Section: Discussionsupporting
confidence: 88%
“…The present the prevalence of malaria based on gender have been widely reported in literature by authors (Okonko et al, 2010;Okafor and Oko-Ose, 2012;Austin et al, 2014;Kuta et al, 2014;Oladeinde et al, 2014;Tela et al, 2015;Umaru and Uyaiabasi, 2015;Ani et al, 2015;Nmadu et al, 2015;Abah and Temple, 2015;Dawaki et al, 2016;Okeke et al, 2016;Garba et al, 2016;Bassey and Nwakaku, 2017). Some author have reported higher prevalence in male (Oladeinde et al, 2014) while other in females (Okonkwo et al, 2010;Tela et al, 2015).…”
Section: Gendermentioning
confidence: 66%
“…Several studies in different location have reported the prevalence of malaria based on locations (Okonko et al, 2010;Okafor and Oko-Ose, 2012;Iloh et al, 2013;Kuta et al, 2014;Austin et al, 2014;Tela et al, 2015;Umaru and Uyaiabasi, 2015;Ani et al, 2015;Nmadu et al, 2015;Abah and Temple, 2015;Dawaki et al, 2016;Okeke et al, 2016;Bassey and Nwakaku, 2017). Level of immunity differs especially in infants.…”
Section: Agementioning
confidence: 99%
“…The results however show that majority of fathers are farmers constituting about 51.5% in the area studied, followed by those with fathers having no occupation, constituting 21.8% (Figure 4). Other finding also reported that majority of Kano residents are farmers and merchants [19].…”
Section: Discussionmentioning
confidence: 84%